Family Resistance in Fighting Radicalism among Youth During the Covid-19 Pandemic in Sompilan, Berbah, Sleman, Yogyakarta - Arfaizar, Januariansyah; Yusdani; Akbar, Ilham; Rizki, Muh. (Universitas Islam Indonesia, 2022)
One element of society that is vulnerable to the influence of radicalism is teenagers or young people known as the